Sex Disparities of Health-related Quality of Life in Moderate to Severe Psoriasis: A Real-world Analysis from the Swiss Psoriasis Registry (SDNTT) - Ramtin Lichtenberger; Lara Valeska Maul; Ion Birkenmaier; Iker Oyanguren; Melike Ak; Kristine Heidemeyer; Christoph Schlapbach; Nikhil Yawalkar; Alexander Egeberg; Simon Francis Thomsen; Jacob P. Thyssen; Christina Sorbe; et al. (Acta Dermato-Venereologica)
Real-world data on gender differences in quality of life among psoriasis patients before and during treatment are scarce. This study analysed data of 748 adults with moderate-to-severe psoriasis enrolled in the Swiss Dermatology Network of Targeted Therapy registry between 2011 and 2023. Quality of life was assessed using the Dermatological Life Quality Index at baseline and at 3, 6, 12, 18, and 24 months. At baseline, women reported significantly lower quality of life than men, with higher Dermatological Life Quality Index scores in the IL-17 inhibitor group (15.0 vs 11.0, p = 0.027), IL-12/23 inhibitor group (7.5 vs 7.0, p = 0.049), and non-biologic therapy group (13.0 vs 9.0, p < 0.001). Although quality of life improved across all subgroups during the follow-up period, women treated with IL-12/23 inhibitors continued to report worse quality of life compared with men after 2 years (p < 0.05), while no significant differences were observed with other therapies. These findings emphasize that women with psoriasis experience lower quality of life at treatment initiation and throughout non-biologic and biologic therapies, underlining the importance of addressing gender-specific differences in the management of psoriasis.